Islamophobia & Muslims‘ religious experiences in the Midwest: proposing critical Muslim theory, a Muslim autoethnography - Abdullah, Mohamad Ridhuan (Kansas State University, 2013)
This study explored Islamophobia and Muslims’ religious experiences in the Midwest. Its purpose was to propose a new theory named Critical Muslim Theory. The research methodology was autoethnography (me, the researcher) in concert with discovering in-depth experiences and narratives of nine Muslim participants (five Muslim females and four Muslim males) in dealing with Islamophobia. Religion became the centrality of Critical Muslim Theory in replacing race (as in Critical Race Theory) while centralizing other oppressions Muslims experience through intersections with religion and law, religion and gender, and religion and race. Critical Muslim Theory represents six basic tenets, namely: (a) Islamophobia is endemic and pervasive, (b) Critical Muslim Theory is critical towards how the dominant society views Islam and Muslims, (c) Islamophobia is a social construction, (d) Legal basis, (e) Intersectionality, and (f) Storytelling and counterstories reveal the oppression and pain of Muslims. An historical context was established for Muslims in the United States of America, although more research needs to be contributed to this area. Instances of interest convergence also were present, however, more research in this area is needed. One recommendation from this research suggests combating ignorance through education and establishing a pure relationship between Muslims and non-Muslims through dialogue for understanding. This study further proposes Muslim Double Consciousness as an area for future research. This topic was of interest due to proposing the theory, its further research and development, and the potential for Critical Muslim Theory to stand on its own as a methodology.
Keywords: Islamophobia; Critical race theory; Critical muslim theory; Autoethnography; Midwest United States; Propose new theory; Islamic Culture (0512); Multicultural education (0455); Religion (0318)